The influence of point defects on the temperature dependence of quasi-two-dimensional 2H-NbSe₂ resistivity - Mamalui, A.A.; Shelest, T.N.; Fatyanova, N.B.; Sirenko, V.A. (Functional Materials, 2005)
The processes of point defects forming in quasi-two-dimensional 2H-NbSe₂ crystals were studied experimentally by measuring the temperature-time resistivity dependencies in the temperature range 300-500 K. It is found out that the special property of (selenium vacancies) formation is the dependence of their formation energy on the time of isothermal exposure, i.e. concentration. Экспериментально исследовались процессы образования точечных дефектов в квазидвумерных монокристаллах 2H-NbSe₂ посредством измерения температурно-временных зависимостей электросопротивления в области температур 300-550 К. Установлено, что характерной особенностью процесса образования точечных дефектов (вакансий селена) является зависимость их энергии образования от времени изотермической выдержки, т.е. от концентрации. Процеси утворення точкових дефектiв у квазiдвовимiрних монокристалах
2H-NbSe₂ дослiджувалися експериментально вимiрюванням температурно-часових залежностей електроопору в областi температур 300-550 К. Встановлено, що характерною особливiстю процесу утворення точкових дефектiв (вакансiй селену) є залежнiсть їхньої енергiї утворення вiд часу iзотермiчної витримки, тобто концентрацiї.